Surface Vs Volume Based Reconstruction of Bone Tissue Using CAS_Annotate and CAS_Navigate - Oliveira, João Fradinho (British Journal of Healthcare and Medical Research, 2017)
Intra-operative systems that provide 3D spatial reasoning support, require 3D models whose geometric accuracy enables the surgeon to make relative positioning and orientation decisions of anatomical structures during navigation. This paper compares the advantages and disadvantages of two popular types of 3D reconstruction from CT polygons, surface based and volume based respectively (Figure 1). Both are implemented in the CAS_Annotate tool, and were used for the purpose of assessing bone tissue modeling strategies for navigation. Their impact in rendering performance is assessed in CAS_Navigate which draws on IGSTK’s intra-operative visualization capabilities.